Corporate Governance Practices Related the Role of Financial Services Authority of Indonesia: A Literature Review Study - Mukti, Aloysius Harry; Istianingsih, Istianingsih (EAJ (Economic and Accounting Journal), 2024)
Based on previous studies, this study aims to explore three focus aspects: the role of the Financial Services Authority of Indonesia (OJK), the investment aspect and the leadership. A qualitative literature review methodology was employed to explore the various aspects of corporate governance. Research Ideas at the intersection of investment and good corporate governance can provide valuable insights into the evolving dynamics of modern financial markets: (1) Impact of ESG criteria on Investment decisions;  (2) Comparative analysis of governance (3) Corporate governance and Innovation Investment; (4) Board Composition and Investment outcomes; (5) Crisis management and Investor relations; (6) Corporate governance and Sustainable finance. Exploring research ideas at the intersection of company leadership and good corporate governance can yield valuable insights into how organizational dynamics influence business success and integrity. Several potential research areas: (1). Leadership styles and Governance outcomes; (2). Digital leadership in corporate governance; (3). Sustainable Leadership and ESG Performance; (4). Technology and Governance Transparency. Through qualitative methodologies derived from recent corporate governance phenomena in Indonesia, the article enriches research outcomes, providing valuable insights for regulators, investors, and decision-makers in Indonesian companies.